Cryogenic spectrometric ellipsometer for studding solid state optical properties - Belyaeva, A. I.; Grebennik, T. G. (SPIE, 1997)
Cryogenic spectrometric ellipsometer (CSE) for studding solid state optical properties was developed. CSE permits determination of the optical constants of solid in the range between 0,3 and 2 micron,in temperature interval from 5 up to 300K. CSE is used for bulk samples characterization and thin films including multilayers stacks analysis (refractive indices and absorption coefficients ( pseudodielectric functions ) and thickness measurement). The special small continuous flow cryostat had been designed for studies in the wide temperature range.The angles of incidence are changed from 45 to 700 discretely by the position of the cryostat windows.
Keywords: cryogenics spectrometric ellipsometer; optical properties; multilayers; continuous flow cryostat; spectroscopy; temperature metrology; refractive index; solid state physics